The relationship between knowledge management practices and employees performance at Perbadanan Nasional Berhad (PNS) / Farah Aida Ahmad - Ahmad, Farah Aida (2017)
Knowledge management is one of the major fields in the current organization in order to improve performance. The aim of this study was to investigate the relationship between knowledge management practices and employees’ performance at Perbadanan Nasional Berhad (PNS). A questionnaire was used as the main instrument for the data collection. A total of 110 respondents answered the questionnaires. It was found that knowledge management practices namely knowledge acquisition, knowledge dissemination and knowledge utilization had positive and significant relationships with employee performance. Thus, in order to achieve higher employee performance, Perbadanan Nasional Berhad has to ensure that the knowledge management practices were excellent.